2022
DOI: 10.1128/spectrum.01653-22
|View full text |Cite
|
Sign up to set email alerts
|

Methanogen Levels Are Significantly Associated with Fecal Microbiota Composition and Alpha Diversity in Healthy Adults and Irritable Bowel Syndrome Patients

Abstract: Hydrogenotrophic microbes play an essential role in the disposal of hydrogen and the maintenance of the hydrogen balance in gut ecosystems. Their abundances vary between individuals and have been reported to be associated with human gut disorders such as irritable bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…This is supported by a humanized gnotobiotic mouse model colonized with Bacteroides thetaiotaomicron and M. smithii, which revealed that co-colonisation with these two microbial species led to higher population densities than when singly inoculated, and that M. smithii enhanced B. thetaiotaomicron to degrade polyfructose-containing glycans [15]. This is supported by the ndings that methanogen levels were positively associated with microbiota diversity in humans as well [20]. However, during the incubations in this study, inhibiting methane production in MEs or adding methanogens into the microbiota of NMEs did not signi cantly alter overall microbiota composition and diversity compared to the control incubations.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This is supported by a humanized gnotobiotic mouse model colonized with Bacteroides thetaiotaomicron and M. smithii, which revealed that co-colonisation with these two microbial species led to higher population densities than when singly inoculated, and that M. smithii enhanced B. thetaiotaomicron to degrade polyfructose-containing glycans [15]. This is supported by the ndings that methanogen levels were positively associated with microbiota diversity in humans as well [20]. However, during the incubations in this study, inhibiting methane production in MEs or adding methanogens into the microbiota of NMEs did not signi cantly alter overall microbiota composition and diversity compared to the control incubations.…”
Section: Discussionmentioning
confidence: 66%
“…These so-called methane excretors (MEs) have a signi cantly higher number of methanogens in the gut with approximately 10 9 CFU/g in stool, whereas individuals who are nonmethane excretors (NMEs) harbor less than 10 4 CFU/g [17,19]. A recent study by Wang et al [20] indicated that methanogen levels were signi cantly associated with overall microbiota composition and diversity, which implies that hydrogenotrophic microbes play an important role in determining the gut microbiota composition and function. However, to what extend the presence of different hydrogen consuming microbes determine the overall microbiota composition and fermentation in MEs and NMEs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the literature shows that SCFAs produced by microbial fermentation induce the same type of effects as increased plasma glucagon-like peptide-1 (GLP-1) and peptide YY (PYY) levels and also stimulate the secretion of gut peptides by acting on specific G-proteincoupled receptors expressed in cells abundant in the colon and terminal ileum [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Using a feedback artificial neural network designed for a certain problem and giving full play to the high-speed computing ability of the computer, the optimal solution may be found quickly. This technology can be applied in clinical medicine to detect the pathogenesis of gastroenterologyneuroscience [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%